Seroprevalence of Chlamydophila felis in cats using the Immucomb ® technique - Troncoso, Ignacio (2023)
Feline chlamydia is a disease caused by Chlamydophila felis, the etiologic agent of feline respiratory complex (FRC) and considered the primary pathogen of conjunctivitis in cats. The objective of the study was to determine the prevalence of the disease in cat patients at a veterinary clinic in the region of Ñuble, Chile, and its association with the variables sex, age group and history of FRC. A blood sample was taken from 60 feline patients who were randomly selected from the total number of registered clinical records. The diagnostic technique used was the immunoenzymatic test ImmunoComb® (sensitivity: 94.7%, specificity: 100%). The seroprevalence of Chlamydophila felis was 51.7% (31/60), with no significant differences by sex, age group, and history of FRC. The results showed the presence of antibodies against Chlamydophila felis in domestic feline patients in the study area.